One of the Effective Methods of Presenting the Text When Teaching Students to Russian as Foreign - Mamadaliyeva F. A. (Web of Journals Publishing, 2023)
This article discusses one of the possible approaches to assessing the content of an oral monologic message, which is based on the reproduction and interpretation of the directly perceived semantic information of the text.
Keywords: problem, presentation, approaches, foreign languages, vocational training, effective method